RFQ cold model RF measurements and waveguide-to-coaxial line transition design for the front-end test stand at RAL - Cheng,Y; Savage,P; Kurup,A; Pozimski,J; Letchford,A (Proceedings of the IEEE Particle Accelerator Conference, 2007)
A 324MHz four vane RFQ cold model has been built, as part of the development of a proton driver front end test stand at the Rutherford Appleton Laboratory (RAL) in the UK. This paper will present the results of RF measurements performed on the cold model, which include analysis of resonant modes, Q-value measurements and electric field profile measurements using a bead-pull perturbation method. These measurements were done before and after brazing of the four vanes and the results were compared to Microwave Studio simulations. Additionally, a tuner has been designed, built and tested and the results will be presented together with the preliminary results of the electromagnetic design of waveguide-to-coaxial line transition structures for the four vane RFQ. ©2007 IEEE.